2020
DOI: 10.3390/su12062387
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Cost Assessment of Electric Vehicles: A Review and Bibliometric Analysis

Abstract: The transportation sector has been reported as a key contributor to the emissions of greenhouse gases responsible for global warming. Hence, the need for the introduction of electric vehicles (EVs) into the transportation sector. However, the competitiveness of the EVs with the conventional internal combustion engine vehicles has been a bone of contention. Life cycle cost analysis (LCCA) is an important tool that can be employed to determine the competitiveness of a product in its early stage of production. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
0
30
0
1
Order By: Relevance
“…Studies on the reliability of NEVs [6], NEVs and smart grids [41], the manufacturing and recycling of lithium batteries [42,43], and the LCC of NEVs [44] found that different manufacturing data selection, lack of timeliness, targets, and modeling selection all affect the authenticity of the results [6]. Presently, review studies tend to study a certain stage, focusing on the energy stage, manufacturing stage, or recycling stage of a product.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the reliability of NEVs [6], NEVs and smart grids [41], the manufacturing and recycling of lithium batteries [42,43], and the LCC of NEVs [44] found that different manufacturing data selection, lack of timeliness, targets, and modeling selection all affect the authenticity of the results [6]. Presently, review studies tend to study a certain stage, focusing on the energy stage, manufacturing stage, or recycling stage of a product.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Netherlands, there is a more favorable income tax rate for people who use low or zero emission company cars for private use (4%) compared to 25% for ICE vehicles. Specifically in Amsterdam, a subsidy scheme was offered for the purchase of frequently used electric vehicles in the city [76]. Denmark, until 1 January 2016, was at the forefront of the European countries with the most sales of battery electric vehicles (BEV), since they were exempt from registration tax, being a great incentive.…”
Section: Renewable Potential and Integration Targetsmentioning
confidence: 99%
“…For PHEVs, the cost reduction achieved by simplifying the design of the internal combustion engine compensates for the cost increase brought about by the introduction of large batteries to some extent. For REVs, the introduction of an internal combustion engine will address the tradeoff between the driving range and battery cost [59,60]. Due to the increasingly stringent laws and regulations, the proportion of BEVs and FCVs will also increase steadily.…”
Section: Prospects For Powertrain Technologies In Chinamentioning
confidence: 99%